A Home away from Home: Defining, Regulating, and Challenging Femininity at the Julia Drummond Residence in Montreal, 1920-1971 - Kirkland, Elizabeth (Urban History Review / Revue d'histoire urbaine, 2006)
As newcomers to Montreal, young single, working women were often subject to low salaries, poor housing options, and unknown dangers—both real and imagined—of a big city. This article considers the Julia Drummond Residence as a place of intersection for two groups of women: the middle-class volunteers who ran the residence and the young, single working women who lived there. While meeting a need in society by providing shelter and food for women earning small salaries, the women running the residence were just as concerned with shaping the femininity and moral fibre of the residents. The practices and ideology of these women, who used the language of reform and renewal, resembled closely those of social reformers of the previous generation, echoing judgment of femininity based on understandings of race, class, religion, and sexuality. This article explores what it was like to live at the residence, how some women found the residence a “home away from home” while others were less comfortable in the unfamiliar and seemingly cold middle-class institution. Positioning themselves as independent citizens of Montreal, at a time when affordable housing became increasingly available, many young, single women asserted their freedom and independence in the years following the Second World War by challenging the regulations imposed on them, and, in so doing, rejected the structured femininity offered to them by institutions such as the Julia Drummond Residence.